2019
DOI: 10.1111/1753-6405.12903
|View full text |Cite
|
Sign up to set email alerts
|

A comparative, retrospective analysis of HIV testing among gay, bisexual and other men who have sex with men in Melbourne, Australia

Abstract: Objective: PRONTO!, a peer‐led rapid HIV‐testing service in Melbourne, Australia, opened to improve HIV testing among gay and bisexual men (GBM). We compared client characteristics and return testing among GBM testing at PRONTO! with GBM testing at Melbourne Sexual Health Centre (MSHC). Methods: All GBM attending PRONTO! and MSHC for HIV testing between August 2013 and April 2016 were included. We describe the number of tests, percentage of clients who returned during follow‐up, the mean number of tests and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The results of the STM indicated that for health-seeking behaviours there were four main locations for STI testing as indicated by the literature [ 23 ] and expert opinion. This includes general practice (GP) clinics, sexual health clinics, community health clinics, and testing in tertiary care.…”
Section: Resultsmentioning
confidence: 98%
“…The results of the STM indicated that for health-seeking behaviours there were four main locations for STI testing as indicated by the literature [ 23 ] and expert opinion. This includes general practice (GP) clinics, sexual health clinics, community health clinics, and testing in tertiary care.…”
Section: Resultsmentioning
confidence: 98%
“…However, gay and bisexual men (GBM) face barriers to accessing these services due to embarrassment with respect to discussing their sexual behaviours with doctors [2] and service provider stigma concerning their sexuality also discourages HIV testing [3]. To reduce these barriers, community-based testing clinics targeting GBM have been implemented in Australia [4–6] and internationally [7,8].…”
mentioning
confidence: 99%
“…13 However, their impact on testing frequency has varied, with peer-based services' reach and scalability limited by predominantly fixed-site models. 14,15 HIV self-testing is a promising additional strategy to increase HIV testing frequency, allowing users to collect, operate, and interpret their own HIV tests when and where they choose. Randomized controlled trials have demonstrated a 2-to 4-fold increase in HIV testing frequency among self-test users, 16,17 and acceptability studies indicate self-tests' convenience, immediacy of results, privacy, less-invasive specimen collection, and a greater locus of control drive actual or intended uptake.…”
mentioning
confidence: 99%
“…Recently, peer-delivered community-based services using rapid point-of-care HIV tests have addressed some of these barriers 13 . However, their impact on testing frequency has varied, with peer-based services’ reach and scalability limited by predominantly fixed-site models 14,15 …”
mentioning
confidence: 99%